The nuances of displacement: foreignness and cosmopolitanism in Eduardo Muslip’s Phoenix (Anclajes, 2016)
The point of view assumed by the narrator of the nouvelles comprising Eduardo Muslip’s Phoenix (2009) assumes variations that collectively could be called a “foreign vision.” Reading the narrator’s positioning in the context of the stranger, as understood by Georg Simmel, demonstrates features of storytelling affected by displacements and distances by familiarizing the distant and estranging the familiar. Understanding the vision of the narrator as a self-reflexive and attentive reveals features of the narrative subject as they relate to contemporary reconsiderations about the new scope of cosmopolitanism. Instead of a depoliticized and uncritical representation of international mobility and spaces of transit in the contemporary world, Muslip gives the various modes of displacement a social and political contextualization.
Keywords: Eduardo Muslip; Argentine Literature; literary criticism; 21st century; nouvelles